Peran Self esteem Dalam Personal branding Pada Pekerja Usia Dewasa Awal - Andini, Tiara Puspa; Verasari, Metty (Psikodinamika: Jurnal Literasi Psikologi, 2026)
The development of the digital economy requires young adult workers to strategically establish their professional image through social media. Personal branding is influenced not only by external factors but also by internal psychological conditions, including self-esteem. This study aimed to examine the association between self-esteem and personal branding among young adult workers. A quantitative approach with a correlational design was applied. The participants consisted of 205 workers aged 20 to 40 years across six provinces in Java Island. Data were collected through an online questionnaire comprising a self-esteem scale adapted from the Rosenberg Self-esteem Scale and a personal branding scale developed by the researcher. Data were analyzed using the Product Moment correlation technique supported by the Monte Carlo method. The results revealed a significant positive relationship between self-esteem and personal branding. Workers with higher levels of self-worth tend to present a more consistent and structured professional image on social media. These findings underscore the importance of strengthening self-esteem to support effective digital personal branding among young adult workers.